Pengembangan Media Video Pembelajaran Tematik Berbantuan Aplikasi Inshot Pada Tema 8 Praja Muda Karana Kelas III SDN 105366 Sei Nagalawan - Nurul Afriza; Dara Fitrah Dwi (Politeknik Kampar, 2024)
This study aims to develop thematic learning media assisted by the InShot application on the theme of 8 young karana students and find out the feasibility and find out how students respond to the development of thematic learning media assisted by the InShot application on the theme of 8 elementary school students of class III SDN 105366 Sei Nagalawan. This study uses the ADDIE development model consisting of five stages which include analysis, design, development, implementation and evaluation. Learning media were evaluated by media expert validators, materials and student responses. The results of media experts get an average score of 88%, material experts get an average score of 73% and student responses get an average score of 92%. The conclusion is that the development of thematic learning video media assisted by the inshot application on the theme of 8 young students because of class III SDN 105366 Sei Nagalawan is feasible to use.